Container-specific pupal productivity for household dengue vector control: A cross-sectional entomological survey in Antang, Makassar, Indonesia - La Ane, Ruslan; Amboi, Wahyulan; Ibrahim, Erniwati; Susilawaty, Andi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Recent urban dengue programs increasingly move beyond larval indices, yet many interventions still underuse container-specific pupal productivity to prioritize household breeding habitats. This study quantified which domestic containers contribute most to Aedes aegypti pupal output in Antang Village, Makassar, to guide targeted and cost-effective dengue vector control at the family level. A cross-sectional entomological survey was conducted in 100 households selected through proportional multistage sampling. All indoor and outdoor water-holding containers were counted and inspected; larvae and pupae were collected, reared for species confirmation, and analyzed using standard entomological indices and container-specific pupal contributions. Of 724 containers examined, 87 (12%) were larva-positive and 72 (10%) were pupa-positive. The House Index was 43%, the Container Index 12%, and the Breteau Index 87, indicating substantial transmission potential. Pupal production was highly concentrated: buckets (39.92% of containers) accounted for 61.11% of pupae, and bath tanks (6.63%) contributed 18.06%, whereas flowerpots/vases were common (38.26%) but produced only 11.11% of pupae; other container types each contributed ≤4.17%. These findings suggest that stable, longer-retention water habitats disproportionately support development to the pupal stage and likely adult emergence. Targeting household actions to buckets and bath tanks—covering, routine draining and scrubbing, improving water-storage practices, and using larvicide only when emptying is not feasible—should deliver the greatest reduction in adult vectors per unit effort while aligning with Islamic family health values emphasizing cleanliness (ṭahārah), prevention of harm, and shared responsibility.